From Mindfulness to Heartfulness : Transforming Self and Society with Compassion. - Murphy-Shigematsu, Stephen (Berrett-Koehler Publishers, Incorporated, 2018)
Explaining how mindfulness can be so much more than a practice for reducing stress, enhancing attention, and instilling tranquility, this book describes eight heartfulness principles that help us realize that the deepest expression of an enlightened mind is found in our relation to others. --